Pharmacokinetics of dipyrone in horses: A multi‐dose, dose escalation study. Issue 6 (6th July 2021) - O'Banion, Melinda Poole; Sundman, Emily; Edmonds, Matt; Davis, Jennifer
Abstract: Dipyrone is a non‐opioid, nonsteroidal anti‐inflammatory drug with antipyretic and analgesic properties commonly used in horses. Dipyrone is rapidly hydrolyzed to the primary active metabolite 4‐methylaminoantipyrine (4‐MAA). The purpose of this study was to determine the pharmacokinetic profile of 4‐MAA following repeated and escalating doses of intravenously administered dipyrone. Twenty‐six horses were randomly allocated to five treatment groups (one placebo group and four dipyrone groups [30 mg/kg q8h, 30 mg/kg q12h, 60 mg/kg q8h, and 90 mg/kg q12h]) and treated for nine consecutive days. Blood was collected at predetermined timepoints, and plasma was analyzed for 4‐MAA concentrations with a validated LC/MS/MS method. Following a single dose, there was a linear correlation to the maximum concentration (Cmax ) achieved. There was a disproportionate increase in the minimum concentration (Cmin ) of 4‐MAA with accumulation occurring at higher doses or more frequent dosing intervals. Significant differences were noted in 4‐MAA Cmax, half‐life, and area under the curve during the dosing interval (AUCtau ) when dipyrone was administered at 30 mg/kg q12h versus q8h. Adverse effects attributed to drug administration were not noted.